Peranan Manajemen Usahatani Tebu Terhadap Produksi di Kecamatan Pintu Rime Gayo Kabupaten Bener Meriah - Bambang Bambang; mayyiskha fitri (Jurnal Agrisep, 2020)
The purpose of this research is to find out the role of management in the cultivation of sugarcane farming which may be caused by costs, unstable prices, lack of government assistance and counseling about sugarcane having an effect on management in the cultivation of sugar cane farmers conducted carelessly or other possibilities that cause production sugar cane bars that are not optimal. Sample farmers were taken as many as 30 farmers using the Purposive Sampling method (deliberately selected) on sugar cane farmers in the District of Pintu Rime Gayo, Bener Meriah Regency. The role of sugarcane farming management on production in Pintu Rime Gayo District of Bener Meriah Regency can be analyzed using the Spearman rank correlation method. The results of the discussion of the number of farm management values are 2,768 with an average value of 92.27 which can be interpreted that farm management in Pintu Rime Gayo District, Bener Meriah Regency has good management. The analysis shows that sugarcane farming management plays a role in the production of sugar cane bars in Pintu Rime Gayo District, Bener Meriah Regency. With a Spearman rank correlation value of 0.777 or 77.70%. The significance rating obtained by t count is greater than t table (thitung ttable) with a value of t arithmetic 6.534 greater than the value of t table 2.048 (6.534 2.048). Reliability and validity test shows that the R table is smaller than the value of the reliability and validity items, which means reliable and valid with a value of R table 0.3494.